Fabrication of Core-Shell PLGA-Chitosan Microparticles Using Electrospinning: Effects of Polymer Concentration - Nguyen Thi Hiep; Nguyen Dai Hai; Vo Van Toi (International Journal of Polymer Science)
This investigation aims to fabricate the core-shell microparticles composed of poly(lactic-co-glycolic acid) and chitosan (PLGA-CS MPs) using electrospinning. The challenge of using electrospinning is that it has many parameters which change product outcome if any single parameter is changed. However, the advantage of this system is that we can fabricate either micro/nanofibers or micro/nanoparticles. To learn about the effect of liquid concentration, the electrospinning parameters (voltage, needle sizes, distance from needle to collector, and ejection speed) were fixed while the concentration of PLGA or chitosan was varied. The results showed that PLGA microparticles can be fabricated successfully when the concentration of PLGA is smaller than 10 wt%. Presence of the chitosan shell was confirmed by zeta potential measurements, FT-IR, optical observation, and fluorescence observation. Thickness of the chitosan shell can be controlled by changing the concentration of chitosan and measured by fluorescamine labeling method. Moreover, SEM observation showed that concentration of chitosan affected the size of PLGA-CS microparticles. The MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay test showed that PLGA-CS microparticles possess excellent biocompatibility.